2015
DOI: 10.1123/pes.2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Training Suppresses Exercise-Induced Lipid Peroxidation and Inflammation in Overweight/Obese Adolescent Girls

Abstract: This study aimed to determine whether aerobic training could reduce lipid peroxidation and inflammation at rest and after maximal exhaustive exercise in overweight/obese adolescent girls. Thirty-nine adolescent girls (14-19 years old) were classified as nonobese or overweight/obese and then randomly assigned to either the nontrained or trained group (12-week multivariate aerobic training program). Measurements at the beginning of the experiment and at 3 months consisted of body composition, aerobic fitness (VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Of the 6478 citations screened after removing duplicates both electronically and manually, 57 studies representing 127 groups (73 exercise, 54 control) and 2792 participants (1667 exercise, 1125 control) met the criteria for inclusion 13–40 42–69 98. The number needed to screen was 0.88% while the NNR was 114.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 6478 citations screened after removing duplicates both electronically and manually, 57 studies representing 127 groups (73 exercise, 54 control) and 2792 participants (1667 exercise, 1125 control) met the criteria for inclusion 13–40 42–69 98. The number needed to screen was 0.88% while the NNR was 114.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published in 45 different journals since 1997 ( trueX- ± SD = 2011±4, median=2012). Fifty-two studies (91.2%) were published in the English language,13 14 16–18 20 22 24–40 42–69 while the remaining five (8.8%) were published in either Chinese19 21 23 98 or Spanish 15. The location in which studies were conducted included 20 different countries, 12 in the USA,24 30 34 35 39 40 46 48 52 56 60 66 8 in China,19–23 38 61 62 98 6 in Brazil,13 15 45 47 58 63 5 in South Korea,36 37 49 55 59 4 in Tunisia,17 25 50 51 3 each in Australia,54 64 65 Canada14 32 57 and Iran,27 29 69 2 in Turkey,33 53 and 1 each in either France,16 Germany,44 Italy,28 Lebanon,68 New Zealand,42 Norway,18 Singapore,67 Sweden,31 Switzerland,26 Taiwan22 or the UK 43.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, whilst some have shown significant increases in peak V O 2 (V O 2peak ) (Owens et al 1999;Gutin et al 2002;Carrel et al 2005;Walther et al 2009), others have reported no change (Gutin et al 1995;Youssef et al 2015). Although differences in the duration, intensity and/or type of exercise programme employed may contribute to this discrepancy, it may also be attributable to differences in baseline fitness levels of the participants, which have been shown to be inversely related to the magnitude of training-induced improvements (Eliakim et al 1996;Mandigout et al 2001).…”
Section: Introductionmentioning
confidence: 93%
“…In terms of overweight/obese individuals though, the available evidence on the role of regular CVE training is limited and contradicting. Specifically, Youssef et al [193] demonstrated that a 3-month multivariate CVE programme prevented the exercise-induced lipid peroxidation and inflammation in overweight/obese girls, possibly via an improvement in body composition. In contrast, Kelly et al [194] reported previously that 8 weeks of CVE training failed to induce any alteration in levels of adipokines (C-reactive protein, interleukin 6, tumor necrosis factor alpha, adiponectin, leptin, and resistin), and oxidative stress markers (8-isoprostane) in overweight children.…”
Section: Regular Cardiovascular Exercise Trainingmentioning
confidence: 99%